Multispecies and individual gas molecule detection using Stokes solitons in a graphene over-modal microresonator - Teng Tan (Nature Portfolio, 2021)
The integration of 2D materials on photonic devices provides advanced functionalities in sensing applications. The authors demonstrate a graphene functionalized microcomb sensor by exploiting spectrally trapped Stokes solitons. They obtain both multispecies gas identification and individual molecule sensitivity.